(untitled) (Research, Society and Development, 2023)
Self-esteem is a term used in psychology to describe how much a person values and likes himself. It is related to satisfaction with one’s own identity, self-confidence and self-esteem. Self-esteem influences choices, behaviors, thoughts and the individual’s own view of value and confidence. The lack of self-esteem may be related to negative affective bonds and problems faced, such as bullying and pressure to fit the aesthetic standards imposed by society. This can lead to negative experiences, undermining one’s success and vitality. Low self-esteem can prevent someone from pursuing their goals, investing in personal and professional projects, and trying new things. The constant exposure of bodies considered perfect can put pressure on and affect people’s personalities. It’s important to remember that beauty is both physical and psychological, and self-care plays a key role in self-esteem. Facial harmonization emerged as a non-surgical alternative to correct facial angles and improve harmony and volume at strategic points. These procedures have gained popularity due to their practicality and convenience. Facial harmonization aims to balance the patient’s face, increasing self-esteem and self-acceptance, as it improves physical appearance. Thus, the objective of this work is to carry out a narrative review of the literature about the relationship between self-esteem and the possibility of maintaining it through orofacial harmonization.